Assumptions and participants in social dialogue regarding digital platforms with an emphasis on Serbia - Kovačević, Aleksandar (Sociološki pregled, 2025)
The aim of this paper is to examine the possibilities of social dialogue on digital platforms and the role of trade unions in protecting the rights of digital workers. The paper starts with the assumption that the digitalisation of work leads to radical changes in the labour sphere, resulting in new forms of employment and regulatory challenges. The analysis covers the definition of the status of digital workers, EU regulations, the position of trade unions, and a case study of Serbia, where digital work is on the rise but under unregulated conditions. The concluding considerations highlight the necessity of social dialogue on digital platforms, which requires amendments to existing labour legislation by expanding the definition of workers, defining platforms as employers, and enabling trade unions to collectively organize these workers.
Keywords: digitalisation; new forms of employment; labour conditions; digital platforms; social dialogue